POLA PERTUMBUHAN DAN NISBAH KELAMIN IKAN BREK (BARBONYMUS BALLEROIDES VALL. 1842) PADA HABITAT YANG TERFRAGMENTASI DI SUNGAI SERAYU JAWA TENGAH - ., Haryono; Rahardjo, MF.; ., Mulyadi; Affandi, Ridwan (JURNAL BIOLOGI INDONESIA, 2014)
A total of 2466 fish were sampled from Serayu River in Banjarnegara, Central Java. The aims of study are to assessthe relationships among length weight, growth, condition factors and sex ratio of of the brek fish (Barbonymusballeroides) with fragmented habitat. The study started from June 2012 to May 2013 using survey mehods. Thestudy sites consist of six stations which were into three segments based on the reservoir position, i.e lower segment(St.1-St.2), middle segment (St.3-St.4), and upper segment (St.5-St.6). The results show length weight relationshipwere W= W= 7.10 -7*L3.084 (r2= 0.97) for all specimens, W = 8.10-6 *L3.061 (r2= 0.96) for males, and W= 7.10-7*L3.089(r2= 0.98) for females; growth pattern were allometric over all condition factor were almost the both males andfemales, i.e. 1.0234 and 1.0275 respectively. Based on the segment, males were the highest in March at the middlesegment i.e 1.2105 (n= 49) and the lowest at was the upper segment i.e. 0.8952 (n = 29). In females, the highestwas also in March at the upper i.e. 1.1895 (n = 19) and the lowest in April at the lower segment i.e. 0.9478 (n=35); sex ratio consists of 1073 males and 1393 females or 1: 1.29.Key words: growth, length-weight relationship, condition factor, and sex ratio